A Review On Finger-Vein Biometrics Identification Approaches - Khalid, Syazana Itqan; Ahmad Radzi, Syafeeza; Mohd Saad, Norhashimah; Abdul Hamid, Norihan; Mohd Saad, Wira Hidayat (Indian Society Of Education And Environment & Informatics Publishing Limited, 2016)
-